Selective Binding of Different Molecular Species of Factor VIII to Isolated Human Platelet Membranes and to Intact Thrombin Stimulated Platelet - Koutts, J.; Zimmerman, T.S. (Thrombosis and Haemostasis, 1979)
Factor VIII is a necessary co-factor in the primary haemostatic interaction between platelets and the subendothelial tissues exposed at sites of vascular damage. We present evidence here of direct binding of factor VIII to isolated human platelet membranes (without the requirement of ristocetin) and to thrombin stimulated intact platelets. This binding is saturable and a function heterogeneity for-factor VIII, corresponding to its known molecular heterogeneity can be demonstrated. Thus, in normal plasma, only the larger molecular forms of VIII:Ag bind to platelet membranes. Various fractions of plasma VIII:Ag enriched in the larger molecular form of VIII:Ag, such as cryoprecipitate, the heavier fraction on sucrose density gradient ultracentrifugation and the void volume fraction of a 4% agarose column show a high percentage of VIII:Ag binding. Conversely the cryosupernatant, the lighter fractions from a sucrose idensity gradient and the VIII: Ag eluting after the void volume fraction of a 4% agarose column show little, if any, :binding to platelet membranes. In patients with typical von Willebrand’s disease, who have reduced levels of qualitatively normal VIII:Ag, a normal proportion of their VIII: Ag binds. In “variant” von Willebrand’s disease, where there is a plasma , deficiency of the larger molecular forms of VIII:Ag and a disproportionately low ristocetin co-factor activity; there is no significant binding of their plasma VIII :Ag. A number of commercial factor VIII concentrates are also shown to be relatively depleted of the large VIII:Ag form and to have a very low platelet binding capacity. Physiologically, thrombin appears :to be an initiator of the factor VIII - platelet interaction.